Educação ambiental como um instrumento para sensibilização ambiental em uma escola municipal de Foz do Iguaçu - PR - Bottan Junior, Osmar Luiz (2013)
This paper focuses on the implementation of strategies for environmental education through workshops on recycling, developed with students of 2nd year of Elementary Education of the City School Professor Elenice Milhorança Foz do Iguaçu - PR. Educational activities involving waste recycling knowledge provide the means to recycle or reuse the waste generated by humans on the environment. The implementation of environmental education to promote these programs in partnership with the recycling program helps to encourage reuse practices and reduction in waste generation, which reaches from encouraging responsible consumption. Thus, the development of awareness projects from the lectures, discussions and workshops on recycling, contribute to form critical citizens regarding the correct disposal of waste. The completion of the recycling project has clarified the students about the many possibilities for the selective collection in the environment contextualizing knowledge of environmental education.